Comprehensive Analysis of the Expression Profiles of Hepatic lncRNAs in the Mouse Model of Alcoholic Liver Disease - Xiaobing Dou; Xiaobing Dou; Xiaobing Dou; Wenwen Yang; Wenwen Yang; Qinchao Ding; Qinchao Ding; Qiang Han; Qiang Han; Qianyu Qian; Qianyu Qian; Zhongyan Du; et al. (Frontiers Media S.A., 2021)
Background and Aim: The worldwide prevalence of alcoholic liver disease (ALD) due to escalating alcohol consumption has presented an unprecedented pressure on human health. A few studies have determined long non-coding RNAs (lncRNAs) involved in the pathogenesis of liver diseases. However, the roles of lncRNAs in ALD development is still poorly understood.Methods: An ALD mouse model was established and confirmed. Expression profiles of lncRNAs were obtained by whole transcriptome sequencing. The altered lncRNAs in ALD mice were further verified by qRT-PCR. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were used to enrich the functions of these lncRNAs. In combination with miRNA and mRNA profiles, we constructed concise endogenous RNA (ceRNA) networks. The function of the most up/downregulated lnRNA was further verified and investigated in both ALD model and AML-12 cells.Results: Totally, five downregulated lncRNAs were obtained and verified in ALD mice. The GO term and KEGG pathway analyses revealed that the identified lncRNAs were associated with alcohol-induced hepatic oxidative damage, cellular inflammation, and lipid metabolism. Combination the differentially modulated miRNAs and mRNAs with ceRNA network analysis, we constructed five ceRNA networks and obtained 30 miRNAs and 25 mRNAs that may participate in ALD. Further, we verified and investigate the function of the most downregulated lnc_1700023H06Rik. Depletion lnc_1700023H06Rik reduced genes encoding for lipid metabolism, especially mRNA Acat2 (ENSMUST00000159697) and Pgrmc2 (ENSMUST00000058578) both in vivo and in vitro. Knocking down lnc_1700023H06Rik induced triglyceride accumulation and lactate dehydrogenase leakage in AML12 cells, consisting with that in alcohol-treated cells.Conclusion: The five remarkably downregulated lncRNAs in ALD mouse model were identified as novel biomarkers, highlighting the key role of lncRNAs in the development of ALD. The effect of lnc_1700023H06Rik plays a pivotal role in lipid deposition and its pathological pathway in ALD needs further investigation.